Stereodivergent Pd/Cu catalysis: asymmetric alkylation of racemic symmetrical 1, 3-diphenyl allyl acetates. Issue 9 (18th February 2021) - Zhao, Ling; Li, Guanlin; He, Rui; Liu, Penglin; Wang, Feijun; Huo, Xiaohong; Zhao, Min; Zhang, Wanbin
Abstract : A stereodivergent Pd/Cu catalyst system was developed, which was successfully applied to the asymmetric allylic alkylation of symmetrical 1, 3-disubstituted allyl acetates with prochiral imino esters in a fully stereodivergent manner. Abstract : We report a stereodivergent Pd/Cu catalyst system that was successfully applied to the asymmetric allylic alkylation of symmetrical 1, 3-disubstituted allyl acetates with prochiral imino esters, providing efficient access to enantiopure products bearing vicinal stereocenters in a fully stereodivergent manner. The protocol proceeds smoothly under mild reaction conditions and can accommodate a range of imino esters, delivering the substituted products in high yields and with excellent diastereoselectivities (up to >20 : 1 dr) and enantioselectivities (up to >99% ee).